Pengaruh Penerapan Proyek Penguatan Profil Pelajar Pancasila (P5) Tema Kewirausahaan Terhadap Jiwa Wirausaha - Hanif Latifah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
P5 entrepreneurship at SMAN 1 Gambiran Banyuwangi has equipped students with the knowledge and skills to become successful entrepreneurs. This study was used to determine the significant effect of the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of entrepreneurship on the entrepreneurial spirit of class X-9 students at SMAN 1 Gambiran Banyuwangi. This study is a study using a quantitative approach. The research sample consisted of 37 students. The data collection method used questionnaires, interviews and documents. The data analysis method used the t-test (partial). The results of the study showed a t-count value of 10.958> t-table (1.690) so it was concluded that P5 entrepreneurship had a significant effect on the entrepreneurial spirit of 77.4% in class X-9 students at SMAN 1 Gambiran Banyuwangi in the 2023/2024 academic year. This activity is expected to continue to apply project-based learning, especially in the context of entrepreneurship so that students' entrepreneurial spirit will continue to develop. Students must be more active, enthusiastic and have the desire to explore more new things so that they can provide satisfactory results.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: Pancasila Student Profile Strengthening Project; Entrepreneurship theme; and Entrepreneurial Spirit